The contribution of immobility risk factors to the incidence of venous thrombosis in an older population. (March 2014) - Engbers, M. J.; Blom, J. W.; Cushman, M.; Rosendaal, F. R.; van, A.
Summary Background Venous thrombosis is common in the older population. Assessment of risk factors is necessary to implement preventive measures. Objectives We studied the associations between immobility‐related risk factors and thrombosis, specifically, hospitalization, surgery, fractures, plaster cast use, minor injuries, and transient immobility at home, in an older population. Patients and Methods Analyses were performed in the Age and Thrombosis, Acquired and Genetic risk factors in the Elderly (AT‐AGE) study, a two‐center population‐based case‐control study. Consecutive cases aged > 70 years with a first‐time thrombosis (n = 401) and control subjects > 70 years old without a history of thrombosis (n = 431) were included. Exclusion criteria were active malignancy and severe cognitive disorders. We calculated odds ratios (OR) with 95% confidence intervals (95% CI) after adjustment for age, sex, body mass index, study center, and population‐attributable risks. Results There was a 15‐fold (OR 14.8, 95% CI 4.4–50.4) increased risk of thrombosis within 2 weeks after hospital discharge. Surgery (OR 6.6, 95% CI 3.7–11.6), fractures (OR 12.7, 95% CI 3.7–43.7), plaster cast (OR 6.2, 95% CI 2.0–18.9), minor leg injuries (OR 1.9, 95% CI 1.1–3.3), and transient immobility at home (OR 5.0, 95% CI 2.3–11.2) were all associated with thrombosis risk over 3 months. The population‐attributable risks for in‐hospital immobility was 27%, and for out‐of‐hospital immobility, 15%. Conclusions In those > 70 years of age, in‐hospital and out‐of hospital immobility are strong risk factors for thrombosis. Additional studies on preventive measures during immobilization in this age group should not focus solely on hospital settings.